2018
DOI: 10.3390/en11071751
|View full text |Cite
|
Sign up to set email alerts
|

Improved Buffering Capacity and Methane Production by Anaerobic Co-Digestion of Corn Stalk and Straw Depolymerization Wastewater

Abstract: A new method has been developed to improve the buffer capacity and methane production of the anaerobic digestion of Corn Stalk (CS), in which both an anaerobic co-digestion of CS with Straw Depolymerization Wastewater (SDW) and a mono-digestion of CS at different substrate concentrations (25.9, 36.2 and 45.3 mg/L) were investigated. Batch assays were conducted under thermophilic conditions for 70 days, which showed that an anaerobic co-digestion significantly increased the buffering capacity and methane produc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 36 publications
1
7
0
Order By: Relevance
“…The lag phase (λ) of five VCRs was within the range of 0-1.109 days. Yang et al reported a longer lag phase (0.7-35.7 days) for codigestion of corn stalk and straw depolymerization wastewater [35]. Theoretically, the inoculum activity, the amount of readily degradable components in the substrate, and the initial pH of the inffluent have a marked impact on the AD start-up time [18].…”
Section: Results Of Linear Regression Analysismentioning
confidence: 99%
“…The lag phase (λ) of five VCRs was within the range of 0-1.109 days. Yang et al reported a longer lag phase (0.7-35.7 days) for codigestion of corn stalk and straw depolymerization wastewater [35]. Theoretically, the inoculum activity, the amount of readily degradable components in the substrate, and the initial pH of the inffluent have a marked impact on the AD start-up time [18].…”
Section: Results Of Linear Regression Analysismentioning
confidence: 99%
“…Anaerobic fermentation is widely utilized in treating corn stovers because it can produce bioenergy and organic fertilizer, meanwhile reducing environmental pollution [3] . However, corn stovers consist of polysaccharides (such as cellulose, hemicellulose and lignin), which form complex structures, consequently resulting in reduced availability of these carbohydrates for enzymatic hydrolysis and subsequent microbial conversion [4] .…”
Section: Introduction mentioning
confidence: 99%
“…Furthermore, pH also plays an important role in the methanation process. And with the proper buffering system optimized pH can be achieved (Gupta and Gupta 2014;Yang et al, 2018). KH 2 PO 4 and NaHCO 3 were considered as the chief components in maintaining the pH of the medium (Eduok et al, 2018).…”
Section: Discussionmentioning
confidence: 99%